Factors Affecting The Entrepreneurial Behavior Of TUMS Research Centers Managers - Mahdi Khayatan; Mohammad Hasan Mobaraki (Tehran University of Medical Sciences, 2014)
Background and Aim: Entrepreneurial roles can be performed by managers at different levels. In fact, entrepreneurship can be interpreted as a tendency adopted by managers towards their environment in which they should have the ability to discover new opportunities for their innovative activities. This study aims to identify factors affecting entrepreneurial behavior of research centers managers at Tehran University of Medical Sciences (TUMS).  Materials and Methods: Considering the sample size determined through Cochran's formula, 90 questionnaires were distributed among TUMS research centers managers. The data were analyzed based on structural equation modeling applying partial least squares approach through Smartpls.2 software.  Results: Of the 90 questionnaires distributed, 67 were acceptable for study. The model created for effective factors enjoyed an acceptable goodness of fit index (GOF=0.49). Factors loading for the observed variables were above 0.4 and the constructs had an acceptable level of reliability and validity.  Conclusion : The results show that contextual and behavioral factors have a positive effect on entrepreneurial behavior and that structural factors have a negative effect on it.